Long‐term biological variability and the generation of a new reference interval for plasma N‐terminal pro‐B‐type natriuretic peptide in Labrador retrievers. (16th April 2020) - Gomart, S.; Allaway, D.; Harrison, M.; Dickson, D.; Seo, J.; Ferasin, L.; Payne, J. R.; Hezzell, M. J.; Borgeat, K.
Abstract : Objectives: First, to investigate the biological variability of N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) in healthy Labrador retrievers and compare this with current laboratory recommendations for dilated cardiomyopathy screening. Second, to calculate a breed‐specific reference interval and validate it in a retrospective cohort. Materials and Methods: Plasma NT‐proBNP was measured in 51 clinically healthy Labrador retrievers at 0, 2, 4, 6 and 8 weeks. Coefficient of variation for individual dogs over time, the coefficient of variation for the group at each time point and the index of individuality were calculated. A reference interval was derived and tested on a clinical dataset available from four UK cardiology referral centres. Results: Median NT‐proBNP was 865 pmol/L (315 to 2064 pmol/L). Mean individual coefficient of variation was 19% (95% CI: 16 to 21%) and group coefficient of variation was 43% (95% CI: 41 to 46%), with index of individuality at 0.44. The breed‐specific reference interval was 275 to 2100 pmol/L. In the validation group, 93% of NT‐proBNP measurements from healthy dogs were within the reference interval. NT‐proBNP measurements exceeded the reference interval in 82% of dogs with dilated cardiomyopathy. The upper bound of the reference interval (2100 pmol/L) had a positive predictive value of 90% and a negative predictive value of 87% for identification of dilated cardiomyopathy in this population. Clinical Significance: Breed‐specific reference intervals might improve the diagnostic accuracy of NT‐proBNP measurement. Applying the currently recommended general cut‐off value to Labradors is likely to result in frequent false positives and diagnosis would be improved by application of the new breed‐specific reference interval calculated here.